Geographical variation in lung function: results from the multicentric cross-sectional BOLD study - Burney, Peter G. (2024)
Spirometry is used to determine what is "unusual" lung function compared with what is "usual" for healthy non-smokers. This study aimed to investigate regional variation in the forced vital capacity (FVC) and in the forced expiratory volume in one second to FVC ratio (FEV1/FVC) using cross-sectional data from all 41 sites of the multinational Burden of Obstructive Lung Disease study. Participants (5,368 men; 9,649 women), aged ≥40 years, had performed spirometry, had never smoked and reported no respiratory symptoms or diagnoses. To identify regions with similar FVC, we conducted a principal component analysis (PCA) on FVC with age, age2 and height2, separately for men and women. We regressed FVC against age, age2 and height2, and FEV1/FVC against age and height2, for each sex and site, stratified by region. Mean age was 54 years (both sexes), and mean height was 1.69 m (men) and 1.61 m (women). The PCA suggested four regions: 1) Europe and richer countries; 2) the Near East; 3) Africa; and 4) the Far East. For the FVC, there was little variation in the coefficients for age, or age2, but considerable variation in the constant (men: 2.97 L in the Far East to 4.08 L in Europe; women: 2.44 L in the Far East to 3.24 L in Europe) and the coefficient for height2. Regional differences in the constant and coefficients for FEV1/FVC were minimal (<1%). The relation of FVC with age, sex and height varies across and within regions. The same is not true for the FEV1/FVC ratio.